2017
DOI: 10.2220/biomedres.38.313
|View full text |Cite
|
Sign up to set email alerts
|

<b>Cordycepin induces apoptotic cell death and inhibits cell migration in renal cell carcinoma via regulation of microRNA-21 and PTEN </b><b>phosphatase </b>

Abstract: Cordycepin is an active component extracted from Traditional Chinese medical herb Cordyceps militaris. Many reports demonstrated that cordycepin harbors antitumor activity in a broad spectrum of cancer types. In this study the actions and the underneath molecular mechanisms of cordycepin were investigated in renal cell carcinoma Caki-1 cell line. Results showed that cordycepin induced apoptotic cell death and inhibited cell migration in Caki-1 cells. Quantitative real-time PCR results and western blot analyses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 46 publications
0
11
0
Order By: Relevance
“…We further examined the effect of cordycepin on OSCAR, cathepsin K and MMP9 mRNA expression levels, where 1 μ M cordycepin significantly downregulated RANKL-induced OSCAR, cathepsin K and MMP activation (Figures 5(c) , 5(d) and 5(e) ). Plus, NFATc1 and cFOS activation were caused by MAPK (mitogen-activated protein kinases) signaling, which is required for early osteoclast differentiation [ 28 , 29 ]. To confirm the molecular mechanism of cordycepin effects on MAPKs following the activation of RANKL in RAW264.7 cells, we investigated the phosphorylation of p38, ERK and JNK using a western blot.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We further examined the effect of cordycepin on OSCAR, cathepsin K and MMP9 mRNA expression levels, where 1 μ M cordycepin significantly downregulated RANKL-induced OSCAR, cathepsin K and MMP activation (Figures 5(c) , 5(d) and 5(e) ). Plus, NFATc1 and cFOS activation were caused by MAPK (mitogen-activated protein kinases) signaling, which is required for early osteoclast differentiation [ 28 , 29 ]. To confirm the molecular mechanism of cordycepin effects on MAPKs following the activation of RANKL in RAW264.7 cells, we investigated the phosphorylation of p38, ERK and JNK using a western blot.…”
Section: Resultsmentioning
confidence: 99%
“…Several research studies have reported that cordycepin plays a function in a multitude of pathologic and physiologic processes, including tumor metastasis, vascular disorder, and brain function [ 28 31 ]. Regarding bone metabolism, cordycepin has been used to prevent oxidative stress-induced bone loss [ 23 , 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Primary vascular smooth muscle cells (VSMCs) were isolated and obtained using a technique combining explant culture and enzymatic digestion from the abdominal aorta of five male Sprague-Dawley rats (age, 3-4 weeks; weight, 80±20 g) obtained from the Laboratory Animal Center of Hebei Medical University (Shijiazhuang, China) as described previously ( 21 ). All animals were housed in a 12 h light/dark schedule in a temperature (22±2°C) and humidity (<40%) controlled room with free access to food and water.…”
Section: Methodsmentioning
confidence: 99%
“… 32 Cordycepin, an adenosine analogue isolated from Cordyceps militaris , downregulated miRNA-21 expression, and thus induced apoptotic cell death and inhibited cell migration in renal cell carcinoma Caki-1 cell line. 33 Therefore, Chinese herbal medicines such as ginsenoside Rb1 and cordycepin may have antitumor activity in a broad spectrum of cancer types through the regulation of specific miRNAs.…”
Section: Effects Of Chinese Herbal Medicines On Mirna Expressionmentioning
confidence: 99%
“… 41 , 42 Cordycepin isolated from Cordyceps militaris could downregulate miRNA-21 expression, and induce apoptotic cell death and inhibit cell migration in renal cell carcinoma cells. 33 It is possible that cordycepin may suppress HCC development through the downregulation of miRNA-21. Similarly, miRNA-25 was also significantly upregulated in HCC clinical samples and stimulated HCC cell growth, migration, and invasion.…”
Section: Potential Role Of Chinese Herbal Medicine–mediated Mirnas Inmentioning
confidence: 99%